(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The development of automated, decentralized, micro-controller machines and procedure measurement techniques is examined in this study. The creation of fault diagnosis techniques, intelligent mechanism strategies, and controller process management are all essential components that are taken into consideration. In this paper, the author elaborates the selection of a certain Microcontroller for a given application is highly challenging. Any developer’s probability of failure or failure is mainly dependent microcontroller that is chosen. This paper provides a concise introduction of the unit and discusses how to choose it for a certain scenario. Microcontrollers are being produced in large quantities by several manufacturers. Comparisons are based on a select group of top manufacturers’ goods. The author concludes that the Requirements for the system, its accessibility, effectiveness, size, power consumption, adaptability, dependability, maintainability, environmental restrictions, software support, accuracy, and safety Following that, it lists three methods that may be used to plan the architecture of monitoring systems networked, scattered, highly coupled